Pitiful giants : presidents in their final terms - Franklin, Daniel P.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Five presidents (Eisenhower, Reagan, Clinton, Bush, and Obama) have been elected to and served a second term. Seemingly free from electoral pressure, each president has taken a unique approach to their second term, and the book seeks to unpack the rationale behind their decisions and actions in their final years of power.
Keywords: Science; Science; Science, general